Cultural Importance Of Useful Plants In Kenduri Sko Traditional Ceremony Of Kerinci Community, Hamparan Rawang Sub-District, Sungai Penuh City, Jambi Province - Adriadi, Ade; Asra, Revis; Wahyuni, Fitra; Marsanda, Firda Dwi; Hikmah , Nurul (BRIN Publishing (Penerbit BRIN), 2025)
Hamparan Rawang District is one of the sub-districts in Sungai Penuh City, Jambi Province which has a culture and tradition. One of the traditional ceremonies in Hamparan Rawang District is the Kenduri Sko Traditional Ceremony or what is called Kenduri Pusako. Assessment of the cultural importance of plant species diversity in Kenduri Sko is useful in ethnobotanical studies which include subsistence activity strategies and traditional classifications. Data collection was carried out by interviewing key informants using the